Awareness of cervical cancer and screening in a Nigerian female market population (2005)
Background: Cervical cancer, although largely preventable, remains a leading cause of cancer death among females in the developing world. The study was aimed at providing useful information on awareness of market women, who are from diverse social backgrounds, about cervical cancer and evaluate U1e extent of utilisation of Papanicolaou's smear by them, It was also aimed at determining the prevalence of risk factors for development of cervical cancer among the population. Methods: TI1is cross-sectional descriptive survey was carried out among market women at Aleshinloye market in November 2003, among 483 randomly selected respondents. A questionnaire probing into their sexual history, awareness about cervical cancer and the extent of utilisation of Pap smear was the survey instrument. Results: The majority (79.5%) of the women were sexually active. One hundred and eighty-six (38.5%) had early sexual debut and 163 (33.7%) had multiple sexual partners. Only 197 respondents (40.8%) were aware of cervical cancer. Of these, 95 (19.7%) were aware of Pap smear as a screening test. The common media of awareness were radio and television (46.6%), public lecture (27.8%) and friends/ relatives (19.9%). However, only 25 respondents (5.2%) have had previous Pap smear done. Conclusion: Though the market women are at considerable risk of developing cancer of the cervix, they are poorly informed about the disease and its prevention. Therefore, there is need for continuous awareness campaign and well-organized screening programmes among this unique category of women.